2010
DOI: 10.1248/jhs.56.31
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Emissions and Toxicity of Polycyclic Aromatic Hydrocarbons from a Heavy-duty Diesel Engine with the Latest Aftertreatment Devices

Abstract: Polycyclic aromatic hydrocarbons (PAHs) bound in particles from automobile emissions may cause adverse human health. In this study, a 3L heavy-duty diesel engine with and without the latest aftertreatment devices were characterized for PAH emissions and toxicity using European Transient Cycle (ETC) and the European Stationary Cycle (ESC). The latest combination of aftertreatment devices including a diesel oxidation catalyst (DOC) and a catalyzed diesel particulate filter (c-DPF) were used to remove diesel exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The high PAH removal efficiencies of the CRT system have been attributed to its ability to both oxidize (DOC component) and filter (DPF component), with the enhanced performance of the SCRT attributed to its ability to break apart heavy hydrocarbons into smaller molecules. 20,25 Other studies have reported similarly high and consistent PAH removal efficiencies for C-DPF-retrofitted engines, 25,37,41,42 whereas other studies have observed more variable removal efficiencies, in particular for the more volatile PAHs. 23,24,28,43 For example, Heeb et al 23 characterized emissions of eight 4-to 6-ring PAHs from a HDDE (6.11 L) operated with two different cordierite-based DPF systems and fuel-borne catalysts (iron-or copper/ironbased).…”
Section: Pahs and Other Organic Speciesmentioning
confidence: 90%
See 1 more Smart Citation
“…The high PAH removal efficiencies of the CRT system have been attributed to its ability to both oxidize (DOC component) and filter (DPF component), with the enhanced performance of the SCRT attributed to its ability to break apart heavy hydrocarbons into smaller molecules. 20,25 Other studies have reported similarly high and consistent PAH removal efficiencies for C-DPF-retrofitted engines, 25,37,41,42 whereas other studies have observed more variable removal efficiencies, in particular for the more volatile PAHs. 23,24,28,43 For example, Heeb et al 23 characterized emissions of eight 4-to 6-ring PAHs from a HDDE (6.11 L) operated with two different cordierite-based DPF systems and fuel-borne catalysts (iron-or copper/ironbased).…”
Section: Pahs and Other Organic Speciesmentioning
confidence: 90%
“…39,[41][42][43]62 In contrast, Tobias et al 74 concluded that diesel nanoparticle mass in engines lacking aftertreatment also contains some sulfate, but is dominated by insoluble elemental carbon and branched alkanes and alkyl-substituted cycloalkanes from unburned fuel and/or lubricating oil, some of which is likely to remain in particulate form. Because the sulfate PM found in NTDE nanoparticles is likely to be relatively soluble in the lung, it is not likely to persist there like the insoluble EC making up a large portion of the PM of TDE nanoparticles (see Figure 3).…”
Section: Impacts Of Aftertreatment On Ultrafine Particle (Ufp) Emissionsmentioning
confidence: 99%
“…In some cases, a 3-fold reduction in DPM has been noted in heavy-duty transit vehicles equipped with DPF ( Tzamkiozis et al, 2010 ). Under more controlled conditions, dynamometer testing of a heavy-duty diesel vehicle equipped with a DOC and DPF showed an average reduction of 96% in the emission of eight PAHs ( Shibata et al, 2010 ). Under some operating conditions, use of DPFs can result in the emission of large numbers of nanoparticulates in the nuclei mode of 30 nm or less; but this finding is the subject of considerable debate, with numerous studies showing a decline in nanoparticulate formation ( Kittelson et al, 2006 ; Hesterberg et al, 2011 ).…”
Section: Factors Affecting Diesel Biomarker Identificationmentioning
confidence: 99%